Analysis of Abdi Kerta Rahardja Union Health Assesment - Indo Yama Nasarudin (Faculty of Economic and Business, 2016)
This study aims to identify and analyse the health assessment union of Abdi Kerta Raharja. Health assessment used measurement and calculation in Rule Deputy Control of Ministry of Union and SMEs of the Republic of Indonesia Number 6 Year 2016. Aspects for health assessment consists the capital aspect, productive asset quality aspects, management aspects, aspects of efficiency, liquidity aspect, the aspect of self-reliance and growth and aspects of the identity of union. Based on the results obtained value for all aspects of health assessment union of Abdi Raharja Kerta is 81.00. It can be concluded that the union of Abdi Kerta Raharja have a healthy category for health assessmentDOI: 10.15408/etk.v15i2.3865